The change of context of traditional Maranao textiles and objects in a contemporary setting - Darjan, Renabelle U. (College of Home Economics, University of the Philippine Diliman, 2015)
ASBTRACT In our constant search for national identity, we were always told to look into our indigenous origins. Among all the other indigenous groups in the Philippines, the Maranaos were the ones who had the most number of interior accessories and art objects, and these are well-documented throughout the years. These Traditional Maranao Textiles and Objects (TMTOs) were still used by both the Maranaos and the non-Maranaos until the present. This study aims to investigate the use or change of use of TMTOs in contemporary domestic settings, and determine their changes in significance and effects to the Maranaos. It uses Grounded Theory methods in gathering the data from 10 Maranao respondents who were selected through convenience sampling, then filtered through purposeful sampling. They were interviewed personally or through a phone call. An inquiry on the use, type of acquisition, value and effects of the TMTOs was conducted. Each interview was recorded, transcribed, translated, then organized in a dummy table. They were categorized and analyzed according to their similarities and differences, and further evaluated for patterns that may occur from the given data. The results indicated that the functions, reasons for using, reasons for value, and effects of TMTOs are interdependent with each other. The main factors that had determined the survival of these TMTOs was the desire of the Maranaos to preserve them. There were three determining factors that affected how TMTOs are valued namely: type of acquisition, social conventions and pecuniary. These had brought about three types of preservation being practiced by the Maranaos today.